Toward a more perfect university - Cole, Jonathan R. (PublicAffairs, 2016)
"A renowned academic leader identifies the ways America's great universities should evolve in the decades ahead to maintain their global preeminence and enhance their intellectual stature and social mission as higher education confronts the twenty-first-century developments in technology, humanities, culture, and economics."--Dust jacket.